2018
DOI: 10.1111/jace.15802
|View full text |Cite
|
Sign up to set email alerts
|

Porosity effect on microstructure, mechanical, and fluid dynamic properties of Ti2AlC by direct foaming and gel‐casting

Abstract: In this study, Ti2AlC foams were fabricated by direct foaming and gel‐casting using agarose as gelling agent. Slurry viscosity, determined by the agarose content (at a fixed solids loading), as well as surfactant concentration and foaming time were the key parameters employed for controlling the foaming yield, and hence the foam porosity after sintering process. Fabricated foams having total porosity in the 62.5‐84.4 vol% range were systematically characterized to determine their pore size and morphology. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Besides, foams O1 and O2 presented slight increases of k 1 and decreases of k 2 with the rise of temperature to 700 °C. Similar trends were observed for freeze cast foams, 55 for gelcasting foams, 56 for porous lanthanum carbide discs, 58 and for SiC granular filters. 38,57 Despite this, no conclusive explanation for this behavior has been proposed so far.…”
Section: Resultssupporting
confidence: 76%
“…Besides, foams O1 and O2 presented slight increases of k 1 and decreases of k 2 with the rise of temperature to 700 °C. Similar trends were observed for freeze cast foams, 55 for gelcasting foams, 56 for porous lanthanum carbide discs, 58 and for SiC granular filters. 38,57 Despite this, no conclusive explanation for this behavior has been proposed so far.…”
Section: Resultssupporting
confidence: 76%
“…Figure 11 shows the interdependence of the pressure drop per unit length with the superficial velocity for all three foam samples examined here. A comparison of simulated results with experimental data is made in the figure that reveals a very satisfactory agreement [8,9]. To be more specific, the quality of the fit of the simulated to the experimental data was measured in terms of a normalized root mean square deviation (NRME) and revealed that the NRME value is 0.028 for the Gelcast93 sample, 0.026 for the Gelcast87 and 0.017 for the Gelcast84.…”
Section: Foam Total Cell Counts Hexahedra Prisms Tet Wedges Polyhedramentioning
confidence: 84%
“…This was accomplished by setting the mean Figure 11. Pressure drop as expressed in References [8,9] vs. superficial velocity for the (a) Gelcast84 foam, (b) Gelcast87, (c) Gelcast93 foams. Comparison of simulation results with experimental data.…”
Section: Foam Total Cell Counts Hexahedra Prisms Tet Wedges Polyhedramentioning
confidence: 99%
See 2 more Smart Citations